Developing opioid prescribing recommendations in the postoperative orthopedic setting - Haddad, PharmD, Daniel K.; Sherman, MD, Orrin H. (Journal of Opioid Management, 2019)
Background: The use of opioid analgesics in the United States has increased nearly fourfold since 1999 resulting in a similar increase in opioid-related overdose deaths. Although the Centers for Disease Control published guidelines for prescribing chronic opioids, there is a lack of guidance for prescribing postoperative opioids. Objective: To offer an evidence-based approach to prescribing opioids for postoperative pain management in the orthopedic setting. Methods: A narrative review was performed of studies evaluating and quantifying opioid use in orthopedic patients in the postoperative setting, as well as studies analyzing patient satisfaction and perception with regards to opioid use. Results: Studies show that postoperative pain may not be the largest contributing factor to developing an opioid use disorder, but rather patient factors such as tobacco and substance use disorder, mental health disorders, anxiety, mood disorders, pre-existing chronic pain, and recent opioid use may play a role. The review also found that most patients do not utilize significant portions of prescribed opioids and most do not require a refill. This trend leaves patients with thousands of unused pills, which are either retained, shared, or diverted. Although there is no guideline for prescribing opioids postoperatively, data suggest that clinicians can prescribe smaller dosages and fewer quantities of opioids initially. There are also non-opioid strategies that can be employed to reduce opioid consumption. Conclusion: There is a need for more high quality research to be conducted to standardize postoperative opioid prescribing patterns and create best practice guidelines to guide clinicians. Orthopedic practices should consider creating institutional guidelines to reduce the amount of opioids prescribed.